Once‐Daily Oxycodone Prolonged‐Release Tablets Are Resistant to Alcohol‐Induced Dose Dumping: Results From a Randomized Trial in Healthy Volunteers. Issue 3 (7th February 2020) - Burger, Nils; Fraser, Douglas; Maritz, Martina Alice; Faulkner, Janice; Rey, Helene
Abstract : The objective of this study was to determine the effect of concomitant alcohol intake on the bioavailability of oxycodone from an oxycodone once‐daily (OOD) formulation and an oxycodone twice‐daily (OTD) formulation. A phase I, open‐label, randomized, crossover alcohol interaction study in 20 healthy volunteers under fasting conditions was conducted. Participants received five treatments, OOD with 240 mL of 0%, 20%, or 40% alcohol; and OTD with 240 mL of 0% or 40% alcohol. Pharmacokinetic parameters did not differ between participants taking OOD with water or with 240 mL of 20% alcohol. There was a slight increase in overall oxycodone absorption from OOD with 40% alcohol but no increase in peak absorption. Oxycodone absorption from OTD showed peak and overall increases with 40% alcohol but maintained a prolonged‐release profile. Although it is recommended that alcohol be avoided while taking opioids, there was no evidence of alcohol‐induced dose dumping in these oxycodone formulations.